Multiple Sclerosis between Genetics and Infections: Human Endogenous Retroviruses in Monocytes and Macrophages - Morandi, Elena; Tarlinton, Rachael E.; Gran, Bruno (Frontiers in Immunology, 2015)
The etiology of multiple sclerosis (MS) is still unknown, but there is strong evidence that genetic predisposition associated with environmental factors can trigger the disease. An estimated 30 million years ago, exogenous retroviruses are thought to have integrated themselves into human germ line cells, becoming part of human DNA and being transmitted over generations. Usually such human endogenous retroviruses (HERVs) are silenced or expressed at low levels, but in some pathological conditions, such as MS, their expression is higher than that in the healthy population. Three HERV families have been associated with MS: HERV-H, HERV-K, and HERV-W. The envelope protein of MS-associated retrovirus (MSRV) from the HERV-W family currently has the strongest evidence as a potential trigger for MS. In addition to expression in peripheral immune cells, MSRV is expressed in monocytes and microglia in central nervous system lesions of people with MS and, through the activation of toll-like receptor 4, it has been shown to drive the production of proinflammatory cytokines, reduction of myelin protein expression, and death of oligodendrocyte precursors. In conclusion, the association between HERVs and MS is well documented and a pathological role for MSRV in MS is plausible. Further studies are required to determine whether the presence of these HERVs is a cause or an effect of immune dysregulation in MS.